Semantic Change of Arabic Loanwords in Indonesian: A Comparative Analysis of Religious and Secular Contexts - Anang Fajar Hasbi; Nurjannah Kasmilah; Muhammad Miftah Fathurrohman; Nining Maida; Sukron Kamil (LISANIA: Journal of Arabic Education and Literature, 2026)
This study examines the semantic changes of Arabic loanwords in Indonesian by comparing their use across religious and secular contexts. The analysis focuses on five Arabic loanwords—īmān, zakāt, ‘ilm, ‘ādil, and ḥākim—which were selected through purposive sampling based on their occurrence across multiple textual sources, morphological productivity, and conceptual significance in Indonesian discourse. Employing a descriptive qualitative approach, the study integrates semantic theory and Hockett’s language borrowing theory. Data were collected from the Kamus Besar Bahasa Indonesia (KBBI), religious texts, public speeches, digital media, and relevant academic literature. The analysis was conducted through identification, classification, and interpretation of contextual meanings. The findings indicate that īmān and ‘ilm have undergone semantic broadening, extending beyond their original religious meanings into wider social, psychological, educational, and intellectual domains. In contrast, zakāt and ḥākim have experienced semantic narrowing due to institutional specialization within religious, legal, and administrative contexts. Meanwhile, ‘ādil has undergone a connotative shift from a predominantly moral-religious concept to a more pragmatic socio-political meaning. From the perspective of language borrowing theory, the findings suggest that these loanwords exhibit characteristics consistent with the processes of adoption, adaptation, and assimilation within Indonesian. The study demonstrates that semantic change in loanwords is shaped not only by linguistic factors but also by social, cultural, and institutional developments. These findings contribute to a deeper understanding of the relationship between language contact, semantic change, and socio-cultural transformation in contemporary Indonesian society.